Analytic Approach to Heteronuclear Decoupling - Garg, Rajat (IISER M, 2015)
Heteronuclear decoupling is a routinely employed resolution enhancement technique in the study of dilute nuclei in NMR spectroscopy. In this thesis, an analytic theory is presented to describe the spin dynamics under continuous wave(CW) decoupling. Employing suitable model spin systems, the intensities and frequencies of transitions are calculated and are compared with simulations emerging from numerical methods.
MS10053
Keywords: Chemistry; NMR; Heteronuclear Decoupling